2015
DOI: 10.14309/00000434-201510001-01521
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Trans-Oral Outlet Reduction in Combination with Gastroplasty (TORe-G) Is a Novel Technique That Is Highly Efficacious and Safe for Weight Loss in Patients With Failed Roux-en-Y Gastric Bypass (RYGB)

Abstract: Background: Enlargement of the remnant gastric pouch and gastro-jejunal (GJ) stoma are associated with weight regain after RYGB surgery. Current evidence suggests an excess weight loss (%EWL) of 12-25% with GJ outlet reduction (TORe) alone. However, the efficacy of a combined approach using endoscopic trans-oral outlet reduction (TORe) in combination with Gastroplasty of the entire gastric pouch from the gastro-esophageal (GE) junction to the GJ stoma (TORe-G) is unknown. ii Methods: Patients who experienced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…At the 12-month mark there was evidence of weight recidivism from 11.34 % TWL at 6 months to 8.55 %. Two studies [24,36] showed persistent weight loss and the rest of the studies demonstrated weight recidivism at 12 months. It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors [11,24,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the 12-month mark there was evidence of weight recidivism from 11.34 % TWL at 6 months to 8.55 %. Two studies [24,36] showed persistent weight loss and the rest of the studies demonstrated weight recidivism at 12 months. It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors [11,24,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 24 36 showed persistent weight loss and the rest of the studies demonstrated weight recidivism at 12 months. It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors 11 24 27 28 . Weight recidivism was reported to be due to genetic factors, lack of dietary compliance, or due to suture breakage/migration leading to dilation of the GJA after TORe 26 27 28 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations